Undergraduates’ Disclosures of Unwanted Sexual Experiences: Who, Why, and When? - Fleming, C. J. Eubanks (Violence against women, 2021)
This study evaluated patterns of sexual assault disclosures as well as the response and impact of that response on assault survivors. The sample consisted of 217 undergraduates with a history of sexual assault (89.5% female, 76.5% Caucasian). Participants reported the order in which they disclosed and the nature and impact of the response they received. Results indicated that the majority of participants told close peers first and perceived the first response to be supportive. These findings are encouraging but also demonstrate the need for improving the response that an assault survivor receives.